Can Wolf Spider Mothers Detect Insecticides in the Environment? Does the Silk of the Egg‐Sac Protect Juveniles from Insecticides?. (24th August 2021) - Laino, A.; Romero, S.; Cunningham, M.; Molina, G.; Gabellone, C.; Trabalon, M.; Garcia, C.F.
Abstract: The use of pesticides for plague control in agroecosystems generates a threat to wildlife and a major problem for human health. Pesticide compounds are also an important source of water and atmosphere contamination. Although insecticides are effective on their target organisms, they often affect organisms that are not their target. The aim of the present study was to research the effects of 3 types of neurotoxic insecticides—a pyrethroid (cypermethrin), a neonicotinoid (imidacloprid), and an organophosphate (chlorpyrifos)—on behavioral and physiological parameters of Pardosa saltans spider (Lycosidae). Our study analyzed for the first time the exploratory behavior of the spider mothers in the presence of these 3 insecticides on their egg‐sacs and also on the ground. We also evaluated the oxidative stress effects on the juveniles hatched in the egg‐sac protected by silk in relation to variations in detoxification enzymes (catalase, glutathione reductase, superoxide dismutase, glutathione‐S‐transferase, and glutathione peroxidase) and lipid peroxidation (reactive oxygen species [ROS]). The results show that these insecticides are repellents for mothers (cypermethrin is the most repellent), and maternal behavior is modified after detection of an insecticide on their egg‐sac but mothers do not abandon their egg‐sacs. These neurotoxic insecticides affect the juveniles inside their egg‐sac. Cypermethrin and chlorpyrifos caused more oxidative stress in juveniles than did imidacloprid. The ROS generated by these insecticides seemed to be adequately eliminated by the juveniles' antioxidant systems. Environ Toxicol Chem 2021;40:2861–2873. © 2021 SETAC